RETRACTED ARTICLE: Malaria in urban, semi-urban and rural areas of southern of Gabon: comparison of the Pfmdr 1 and Pfcrt genotypes from symptomatic children - Sydney Maghendji-Nzondo; Lady-Charlène Kouna; Gaël Mourembou; Larson Boundenga; Romeo-Karl Imboumy-Limoukou; Pierre-Blaise Matsiegui; Rella Manego-Zoleko; Bertrand Mbatchi; Didier Raoult; Fousseyni Toure-Ndouo; Jean Bernard Lekana-Douki (Malaria Journal)
Abstract Background Artesunate-amodiaquine (AS-AQ) and artemether-lumefantrine (AL) are first- and second-line treatments for uncomplicated Plasmodium falciparum malaria in Gabon. AL remains highly efficacious, but its widespread use has led to molecular selection of the NFD haplotype on Pfmdr1 and K76 in Pfcrt. In this study, plasmodial infection characteristics and the distribution of the Pfmdr1 and Pfcrt genotypes involved in reduced efficacy of artemisinin-based combination therapy (ACT) were investigated in four Gabonese localities. Methods A cross-sectional study was conducted in the paediatric units of rural (Lastourville and Fougamou), semi-urban (Koula-Moutou) and urban (Franceville) areas. Malaria was diagnosed with the rapid diagnostic test Optimal-IT® and confirmed by blood smear. Pfmdr1 codons 86, 184 and 1246 and Pfcrt codon 76 were genotyped by PCR–RFLP and sequencing. Results Among 1129 included children, the prevalence of plasmodial infection was 79.5 % at Lastourville, 53.6 % at Fougamou, 36.1 % at Koula-Moutou, and 21.2 % at Franceville. The prevalence was significantly higher among children over 60 months of age in both semi-urban (p = 0.01) and urban (p = 0.004) areas. The prevalence of Pfmdr1 wild-type N86 differed significantly between Lastourville (57.8 %) and Koula-Moutou (45.4 %) (p = 0.039). No difference in 184F-carrying parasites was found between Lastourville (73.8 %), Fougamou (81.6 %), Koula-Moutou (83.2 %), and Franceville (80.6 %) (p = 0.240). The prevalence of wild-type D1246 was significantly different between Lastourville (94.1 %), Koula-Moutou (85.6 %) and Franceville (87.3 %) (p = 0.01). The frequency of wild-type K76 was not significantly different across the four sites: Lastourville (16.5 %), Fougamou (27.8 %), Koula-Moutou (17.4 %), and Franceville (29.4 %) (p = 0.09). The mixed genotypes were only found in Lastourville and Franceville. The NFD, YFD and NYD haplotypes were mainly Lastourville (46.6, 25.8, 14.0 %), Fougamou (45.5, 9.1, 42.4 %), Koula-Moutou (35, 6.7, 40.4 %), and Franceville (40.0, 16.0, 32.0 %). Conclusion This study shows an increase in the prevalence of childhood plasmodial infection in Gabon according to the low socio-economic level, and a high frequency of markers associated with AL treatment failure. Close monitoring of ACT use is needed.